Pembelajaran Berbasis Digital kepada Guru di SMP Negeri 3 Kecamatan Huamual Kabupaten Seram Bagian Barat - Rhaishudin Jafar Rumandan; Kapraja Sangadji; Muhammad Kashai Ramdhani Pelupessy (IAIN AMBON, 2022)
The digital-based learning workshop aimed to train teachers at SMP Negeri 3, SMA Negeri 9 Huamual District, West Seram Regency in an effort to improve teacher professionalism in responding to the challenges of changing times. This service to teachers uses training and workshop methods. Participants in this activity were 30 teachers from SMP Negeri 3 and SMA 9, Huamual District, Seram Regency. The output of this workshop is that participants have been able to design digital-based learning media and are able to use them in the learning process at school.Keywords: Digital Learning, Teacher, Seram Bagian Barat